Classification of residential buildings in Cyprus based on their energy performance - Maxoulis, Christos N.; Kalogirou, Soteris A.; Florides, Georgios A.; Panayiotou, Gregoris; Papadopoulos, Agis; Neophitou, Marina; Fokaides, Paris A.; Georgiou, Georgia; Symeou, A.; Georgakis, G. (My University, 2009)
The significance of the building sector in terms of energy consumption is well acknowledged. Scientific studies have shown that the potential of energy savings in the building sector is quite significant. In this view the knowledge of how the building stock of Cyprus behaves in terms of energy consumption is quite valuable. This knowledge will assist policy makers to formulate targeted measures aiming the improvement of energy efficiency and will provide valuable information for setting current legal standards and benchmarks in the energy performance certificate, a requirement of the 2002/91/EC Directive. Unfortunately, the existing knowledge on this subject is quite poor. As a remedy, and in order to improve our knowledge on the subject, a research project supported by the Research Promotion Foundation under the 2008 call is in operation since December 2008. This study will present the outline, the goals and the proposed methodology of the research project “Classification of buildings in Cyprus based on their energy performance” and will exhibit the initial findings of the survey questionnaire regarding the energy behavior and other characteristics of the residential building stock of Cyprus.
Keywords: Directive 2002/91/EC; Residential Building Stock; Energy behavior; Statistics